Maximizing cost savings and clinical outcomes: A retrospective analysis of antimicrobial stewardship for meropenem utilization in Saudi Arabia - Rawan T. Tafish; Reem Al-Zayer; Faisal Al-Anazi; Jida Al-Mulki (PLoS ONE, 2025)
Background Meropenem, a key antibiotic for multidrug-resistant infections, is often misused, leading to antimicrobial resistance, increased healthcare costs, and excessive consumption. Optimizing its use through antimicrobial stewardship program is crucial to improving clinical outcomes, reducing resistance, and minimizing unnecessary expenditures. Objectives To evaluate trends in meropenem utilization, compliance, consumption, and cost across consecutive quarters from April 2022 to December 2023, highlighting the impact of the gradual implementation of antimicrobial stewardship guidelines and the pivotal role of clinical pharmacists in improving patient outcomes. Methods A retrospective observational study was conducted in a tertiary-care private hospital in Saudi Arabia between April 2022 and December 2023. Meropenem utilization was assessed quarterly based on predefined key indicators to evaluate compliance with antimicrobial stewardship guidelines; Q1-2022 served as a baseline for comparison. Consumption was measured in defined daily doses (DDD) per 1,000 patient-days, and cost analysis was performed using Antimicrobial Cost Per Patient Day (ACPD). The main outcome measures included clinical improvement within 72 hours and transfer or discharge in good clinical condition. Results Overall compliance with antimicrobial stewardship program guidelines improved significantly from 85.7% in 2022 to 100% in 2023 (p = 0.02). Specific indicators showed substantial progress: compliance with drug interaction considerations increased from 93.8% (123/131) to 98.7% (157/159), appropriate duration compliance rose from 68.3% (82/120) to 90.3% (112/124), and adherence to culture follow-up interventions improved from 51.2% (43/84) to 81.7% (67/82) (all p < 0.05). However, compliance with appropriate dosing declined significantly from 89.3% (117/131) to 82% (123/150). By late 2023, enhanced compliance correlated with better clinical outcomes. Meropenem consumption decreased by 47%, resulting in cumulative savings estimated at 554,285 Saudi Riyals (S.R.), with expenses reduced to approximately 56,365.19 S.R. Conclusion The phased implementation of an Antimicrobial Stewardship Program in the clinical setting effectively optimized meropenem use, reducing consumption and costs, and improving prescribing practices and patient outcomes.